Incidence and Predictors of Anemia Among Children on Antiretroviral Therapy at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2007–2017: A Retrospective Follow-Up Study - Techane MA (Dove Medical Press, 2020)
Masresha Asmare Techane,1 Degefaye Zelalem Anlay,2 Eleni Tesfaye,2 Chilot Desta Agegnehu3 1Department of Pediatrics and Child Health Nursing, School of Nursing, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Community Health Nursing Unit, School of Nursing, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3School of Nursing, College of Medicine and Health Sciences and Comprehensive Specialized Hospital, University of Gondar, Gondar, EthiopiaCorrespondence: Chilot Desta AgegnehuSchool of Nursing, College of Medicine and Health Sciences and Comprehensive Specialized Hospital, University of Gondar, Gondar, EthiopiaTel +251 918627403Email Chilotdesta@gmail.comBackground: Anemia is the most common hematological abnormality among children on antiretroviral therapy. In Ethiopia, as far as our search, there are no studies done on the incidence and predictors of anemia among children on antiretroviral therapy. This study aimed to assess the incidence and predictors of anemia among children on antiretroviral therapy, attending antiretroviral therapy care at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, from 2007 to 2017.Methods: A retrospective follow-up study was conducted among 391 children on antiretroviral therapy. Mean survival time for children to be anemia free was estimated. A Log rank test was used to compare survival curves among different independent variables. The Cox regression model was used. The adjusted hazard ratio (AHR) with a 95% confidence interval (CI) was calculated. P-value ≤ 0.05 was considered as statically significant.Results: The overall incidence rate of anemia was 10.5 (95% confidence interval (8.6, 12.8)) per 100 child-year. Being severe-immunosuppressed (AHR=2.9, 95% CI: 1.23– 6.77), undernutrition (AHR =2.7, 95% CI: 1.5– 5), taking zidovudine-based ART regimen (AHR =4, 95% CI: 1.23– 12.9), and tuberculosis (AHR =2.1, 95% CI: 1.4– 3.3) were independent predictors of anemia among children.Conclusion: In this study, the incidence rate of anemia among children on antiretroviral therapy was found to be high. Tuberculosis, zidovudine-based drugs, severe immunosuppression, and undernutrition have remained statically significant predictors of anemia among children on antiretroviral therapy. Children with HIV were the most vulnerable group for anemia, especially in developing countries. Therefore, improving their nutritional status and considering other predictors of anemia were very important for children to reduce the incidence of anemia among children with HIV.Keywords: anemia, anti-retroviral therapy, children, Ethiopia, incidence